Factors That Influence the Development of Governmental Accounting in Malaysia - Saleh, Zakiah (Asian Journal of Accounting Perspectives, 2008)
Governmental accounting is affected by its context, which includes economic development, political stance and individual perceptions. Change and development in government accounting is often associated with public sector reforms. Since accounting is central to the financial management of any organisation, reforms in the public sector would also have an impact on public sector accounting and reporting practices. Accounting and reporting practices need to accommodate the changes in how public sectors are managed. Hence, reforms in governmental accounting and reporting are part of the overall reform in the public sector. As in other countries, the Malaysian public sector has also been undergoing reforms. This study attempts to obtain opinions and perceptions on the factors that have contributed to the development of the Malaysian governmental accounting and on the implications of changing the current accounting system. A total of 20 interviews were conducted with government accountants, government auditors, policy makers and representatives of professional accounting bodies in Malaysia. Unlike in other countries such as Australia, financial crisis did not result in any change to the accounting system in Malaysia. Respondents to the interview survey were of the opinion that the Treasury, including the Accountant General’s Department played major roles in the development of governmental accounting in Malaysia. To a lesser extent, the politicians and technological change could also have an impact on the Malaysian governmental accounting. Respondents of the survey are of the opinion that accrual accounting is relevant to the Malaysian governmental accounting.